Effects of the Novel Coronavirus Pandemic on the Identification and Care of Critically Ill Emergency Patients Not Infected with COVID-19 - Zhu MY; Li R; Xu J; She F; Du X; Zhang W (Dove Medical Press, 2023)
Ming-Yue Zhu,* Rong Li,* Jie Xu, Fei She, Xin Du, Wei Zhang Department of Emergency Medicine, the Fourth Medical Center, Chinese PLA General Hospital, Beijing, People's Republic of China*These authors contributed equally to this workCorrespondence: Wei Zhang, Department of Emergency Medicine, the Fourth Medical Center, Chinese PLA General Hospital, No. 51 Fucheng Road, Haidian District, Beijing, 100048, People's Republic of China, Tel +86 010-66867373, Email zhangw8642@126.comObjective: To clarify variations of diagnosis and treatment in the emergency care of critically ill patients not infected with novel coronavirus (COVID-19) prior to and amidst the COVID-19 pandemic.Methods: A retrospective cohort study was conducted to compare and analyze the diagnosis and treatment data of critically ill patients with non-COVID-19 infection who were admitted to the emergency department of the Fourth Medical Center of Chinese PLA General Hospital from January 2019 to November 2022. The variations in emergency care of the pandemic were summarized, and the influence of the pandemic on emergency care was assessed.Results: A total of 6634 critically ill patients with non-COVID-19 infection were included in this study. These patients were elderly, high incidence of chronic diseases, and extended emergency duration during the pandemic. Notably, the proportion of patients requiring intensive care was twofold higher compared to the period before the pandemic. Throughout the pandemic, patients experienced prolonged emergency durations, increased overall costs and daily expenses per patient. Further investigation revealed that elderly patients exhibited worse medical conditions, requiring lengthier emergency treatment and incurring escalated healthcare expenses. However, the presence of pre-existing chronic diseases did not appear to influence disease severity, nor extended emergency durations or heightened healthcare expenditures. Irrespective of the pandemic phase-be it short-term, medium-term, or long-term emergency care-greater healthcare spending was necessary.Conclusion: There was no difference in the disease spectrum of emergency critical ill patients with non-COVID-19 infection prior to and amidst the COVID-19 pandemic, nor the duration and expenditure in prior chronic illness patients. However, the disease severity and emergency duration have led to an increase in the total cost and economic intensity of emergency care for all patients during the epidemic. Especially, elderly patients required longer emergency duration, greater healthcare spending, and more inpatient medical resources than usual.Keywords: novel coronavirus epidemic, emergency, elderly